2021
DOI: 10.1088/1755-1315/716/1/012122
|View full text |Cite
|
Sign up to set email alerts
|

Life Cycle Assessment of a combined cycle power plant in Indonesia

Abstract: This paper presents the Life Cycle Assessment (LCA) of a 640 MW combined cycle power plant located in West Java, Indonesia. The power plant adopts the dual-fuel firing system, in which both natural gas and high-speed diesel fuels are used. The LCA was performed using the open-source LCA software OpenLCA version 1.9. A functional unit of 1 kWh of electricity generation was used in calculating the environmental impacts. The system boundary was modeled using the gate-to-gate system, which includes all inputs and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…The accumulation of plastic debris in urban waterways, landfills, and coastal areas poses significant ecological and public health risks, necessitating urgent action to mitigate its impact [6], [13]. Plastic waste management in Indonesia is relatively poorly implemented due to the limited number of recyclers, highlighting the need for alternative solutions such as converting plastic waste to paving blocks [14]. The regulation of International Law and National Law plays a crucial role in protecting the marine environment and preventing environmental pollution caused by plastic waste [7].…”
Section: Plastic Waste Pollution In Urban Areasmentioning
confidence: 99%
“…The accumulation of plastic debris in urban waterways, landfills, and coastal areas poses significant ecological and public health risks, necessitating urgent action to mitigate its impact [6], [13]. Plastic waste management in Indonesia is relatively poorly implemented due to the limited number of recyclers, highlighting the need for alternative solutions such as converting plastic waste to paving blocks [14]. The regulation of International Law and National Law plays a crucial role in protecting the marine environment and preventing environmental pollution caused by plastic waste [7].…”
Section: Plastic Waste Pollution In Urban Areasmentioning
confidence: 99%
“…The OpenLCA v.1.8.0 software was used in the study to model the Contact Smart Card and environmental impact assessment using CML-IA (baseline) method [15][16], the baseline is the most common impact category used in LCA [17]. The following impacts are considered: Human toxicity, Fresh water aquatic ecotox, Eutrophication, Marine aquatic ecotoxicity, Acidification, Global warming (GWP100a), Ozone layer depletion (ODP), Photochemical oxidation, Terrestrial ecotoxicity, Abiotic depletion and Abiotic depletion (fossil fuels) [18] as shown in Table 2.…”
Section: Lifecycle Impact Assessmentmentioning
confidence: 99%